The natural history and predictors of persistent problem behaviours in cystic fibrosis: A multicentre, prospective study - Glazner, J; Hay, M; Jaffe, A; Massie, J; Hiscock, H; Sheehan, J; Armstrong, David (My University, 2012)
ABSTRACT Background In cystic fibrosis (CF), problems with sleep, eating/mealtime behaviours, physiotherapy adherence and parental mental health issues are common, yet their natural history and the extent of service use to address them are unknown. Objective Follow up the 2007 cohort to determine:(1) prevalence of child sleep, eating/mealtime behaviours, physiotherapy adherence, and externalising/internalising problem behaviours and primary caregiver mental health status after a 3-year period; (2) natural history of child behaviours; (3) potentially modifiable predictors of persistent problems; and (4) service use for behaviours. Design Prospective cohort. Setting: Royal Children’s Hospital, Monash Medical Centre and Sydney Children’s Hospital (Australia) CF clinics. Participants Caregivers, of children aged 3–8 years, who completed the baseline questionnaire. Main outcome measures Child sleep, eating/mealtime behaviours, adherence with therapy and externalising and internalising behaviours. Predictors: parenting style (low warmth), caregiver mental health status and sleep quality at baseline. Results 102 of 116 (88%) families participated. The prevalence of sleep and eating/mealtime problems at follow-up was similar to baseline. The prevalence of caregiver mental health symptoms remained higher than the community data. 71 out of 102 (70%) of the children experienced at least one persistent behaviour problem. Caregiver mental health difficulties predicted persistent child moderate to severe sleep problems (adjusted OR 6.5, 95% CI 1.2 to 36.2,p=0.03) and their persistently poor adherence to the physiotherapy regimen (adjusted OR 3.5, 95% CI 1.3 to 9.2, p=0.01). Conclusions Child problem behaviours are common in children with CF, persist and are often predicted by the mental health of the parent. Routine surveillance for and management of child problem behaviours are recommended
Archives of Disease in Childhood
Keywords: Families -- Parents and Parenting; Health -- Physical; Health -- Mental; Child Development -- Behaviour; Childhood and child development; Families and relationships; Health and wellbeing; Child Development; Families; Health; Mental; Physical; Behaviour; Parents and Parenting; Families and relationships; Childhood and child development; Health and wellbeing